Differentiated Learning Strategies for Enhancing Early Childhood Independence: A Case Study - Prastyo, Danang; Suryanti; Heryanto Susilo; Desika Putri Mardiani; Ardhana Reswari (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
This study examines how differentiated learning strategies contribute to the development of independence among children aged five to six at TK Al-Islam Bangkalan, a rural kindergarten in East Java, Indonesia. Using a single instrumental case study design, data were collected over four months through non-participatory observation, semi-structured interviews, and document analysis, and analyzed using the Miles and Huberman model. Findings indicate that variations in content and process, supported by predictable routines and consistent teacher scaffolding, enabled most children to select learning materials and choose appropriate task difficulty. At the same time, a minority continued to require validation. Product differentiation and systematic assessment remained limited, reflecting constraints in teacher assessment literacy, time allocation, and class size. The study demonstrates the pedagogical potential of differentiated learning to foster initiative, responsibility, and self-confidence in low-resource early childhood settings. It highlights the necessity of practical, context-sensitive implementation strategies. The research provides evidence that differentiation principles can be adapted to rural and collectivist educational contexts and can inform discussions on culturally responsive pedagogy and equitable early childhood practice. Limitations include single-site sampling, reliance on teacher reports, and incomplete assessment artifacts, all of which limit generalizability. The study is significant for policy and practice because it links Merdeka Belajar (Freedom to Learn) objectives to observable developmental outcomes and identifies concrete barriers to scaling differentiated approaches. Recommended actions include targeted professional development on formative assessment and product differentiation, design-based collaborations to co-create feasible rubrics with teachers, and multi-site longitudinal studies to evaluate transferability and sustained impact on independence.